Social media very widely used, but use for news and information about COVID-19 is declining - Fletcher, R; Kalogeropoulos, A; Nielsen, R (Reuters Insitute for the Study of Journalism, 2020)
In this RISJ Factsheet we examine people’s use of social media as a source of news and information during the coronavirus pandemic in the UK. This is the sixth in a series of ten factsheets based on an ongoing online panel survey of a representative sample of the UK population, fielded from 18 June to 24 June 2020. We find that: (i) the use of social media in general has remained consistent during the coronavirus pandemic, but the use of many social networks specifically for news and information about COVID-19 fell from April to June, (ii) with Facebook and Twitter (both used by 12%) the social networks most widely-used for news and information about COVID-19, and with fewer people saying they use YouTube (5%), WhatsApp (3%) and Instagram (4%). However, (iii) around 10% say that they trust news and information about COVID-19 on social media, video sites and messaging apps.